A new way of evaluating the biomechanics of the mandible with freedom in three axes in space: Technical note - Meira, Josete Barbosa C.; Landgraf, Higor; Shinohara, Elio Hitoshi [UNESP]; Luz, Joao Gualberto C.; Ballester, Rafael Yague (Elsevier B.V., 2018)
Objective: A biomechanical analysis of fixation devices to repair fractures or osteotomies of the mandible is carried out in hemi-mandibles fixed in the condylar process, the force is applied in the molar region and a single movement is allowed. This technical note presents a new setup for evaluating the biomechanics of the mandible with the following improvements: (1) providing freedom of mobility in three axes in the space; (2) applying forces in a way that closely replicates that of real cases; (3) capable of evaluating the fracture resistance and the stiffness and elastic recovery. Method: A rigid metal support mounted on bearings was developed that allowed the movement and deformation of the mandible during load application to mimic its freedom of movement when in function. Steadying was only in the mandibular fossae and free in all other regions. Ten fresh sheep mandibles were subjected to testing of their rigidity and capacity for elastic recovery after a displacement of 0.75 mm. Results: After three displacement cycles, the mean value of stiffness was 506 +/- 64 N/mm, and the mandibles showed visco-elastic recovery. Conclusion: This new apparatus and approach is promising for use in the evaluation of mandibular fixations.
Keywords: Mandible; In vitro techniques; Apparatus and instruments; Elasticity